Literasi Digital Sebagai Instrumen Pencegahan Cyberbullying Dalam Pembelajaran PKn di Sekolah Dasar: Sebuah Kajian Literatur - Putu Dian Handayani; Dewa Bagus Sanjaya; I Nengah Suastika (Jayapangus Press, 2026)
The rapid development of digital technology has increased the risk of cyberbullying among elementary school students, yet the integration of digital literacy into Civic Education (Civic Ed) as a preventive measure remains underexplored. This study aims to analyze the role of digital literacy as an instrument for preventing cyberbullying in Civic Ed learning at the elementary level and to offer theoretical contributions to digital citizenship concepts. A qualitative systematic literature review was employed. Data were sourced from Google Scholar, ERIC, Scopus, Taylor & Francis Online, and DOAJ (2020–2026). Inclusion criteria: (1) focus on ages 7–12, (2) discussion of at least two variables (digital literacy, cyberbullying, Civic Ed), (3) indexed at least Sinta 2 or Q3. From 187 initial articles, after three-stage selection and snowballing, 30 journal articles, 7 policy documents, and 5 academic books were analyzed. Findings indicate that cyberbullying is a multidimensional challenge not yet optimally addressed in the elementary Civic Ed curriculum. The novelty lies in the proposed Three-Pillar Integration Model (MITRA) and the Digital Literacy Integration in Civic Ed Model (MILD-PKn), positioning digital literacy as a moral and social instrument not merely a technical one. The main contribution is strengthening Civic Ed as a space for developing Pancasila-based digital citizenship. The study concludes that strengthening digital literacy in Civic Ed learning is a preventive strategy against cyberbullying while shaping critical, ethical, and responsible digital citizens from an early age.